Visual outcome in open globe injuries - Thevi, T; Mimiwati, Z; Reddy, S C (Nepalese Journal of Ophthalmology, 2012)
Objective: To determine the factors affecting the visual outcome in patients with open globe injuries of eye. Materials and methods: In a prospective interventional study of consecutive patients with open globe injuries, the age, gender, place of injury, object causing injury and safety precautions taken were recorded. A detailed examination of the eye was done with a slit-lamp. X-rays of the orbits were taken in order to determine the presence of a foreign body. The injuries were classified as simple or complicated depending on the involvement of the pupil/iris, lens and retina. Finally, post operative best-corrected visual acuity at last follow up was noted. Results: Fifty-two patients (52 eyes) were included in the study. The mean age of patients was 27.25±12.62 years (range 9-73 years). The majority of injuries occurred in the workplace (36.5%); nail (15.4%) and glass (15.4%) were the most common objects causing injury. Of those with good initial visual acuity, 90% maintained good visual outcome. Patients with corneal lacerations of less than 5 mm had significant good visual outcome. The number of corneal lacerations and visual axis involvement did not affect the visual outcome. Those with corneoscleral lacerations had significantly poor visual outcomes compared to those with corneal or scleral lacerations alone. Conclusion: Predictors of good visual outcome are good initial visual acuity, a corneal laceration wound of less than 5mm, a deep anterior chamber, and simple lacerations. Age, gender, place of injury, object causing injury, presence of hyphema or intraocular foreign body, and the use of safety precautions did not affect the visual outcome. DOI: http://dx.doi.org/10.3126/nepjoph.v4i2.6542 Nepal J Ophthalmol 2012; 4 (2): 263-270